An electricity generation means. - Misron, Norhisam; Jelani, Abdul Razal; Masruni, Norafiza; Azian, Mohd Syafiq (2009)

(untitled)
An electricity generating means providing a stator (101), wherein the stator includes a plurality of slots (102), wherein the slots are disposed in an annular placement circumferential within the stator, a rotor (103), wherein the stator annularly encloses the rotor, a plurality of magnets (105), wherein the magnets are embedded in the rotor, wherein the magnets are disposed next to an air gap (112) around the outer circumference of the rotor, wherein the magnets have a polarity wherein north pole of the magnet is disposed proximate to the centre shaft so as to provide required flux flow (111) and a plurality of coil windings (107), wherein the coil windings are wound around a plurality of teeth in the stator.